Value creation attempts via photographs in sustainability reporting: a legitimacy theory perspective. Issue 2 (17th September 2020) - Ali, Irshad; Lodhia, Sumit; Narayan, Anil K.
Abstract : Purpose: This paper aims to investigate the use of legitimacy strategies via the usage of photographic disclosures in sustainability reporting as an attempt towards creating value. Design/methodology/approach: This study used visual content analysis to identify disclosure trends and value creation themes from sustainability-related photographs in the annual and sustainability reports of Fonterra Co-operative Group over a ten-year period. The findings were interpreted using legitimacy theory. Findings: The findings show a significant increase in the usage of photographs to legitimise and reinforce the organisation's sustainability messages. The photographs are dominated by images signalling to stakeholders' positive sustainability messages, as a systematic method for managing stakeholder expectations to maintain, gain and even repair legitimacy. A majority of photographs have supporting textual narrative, which could be construed as an attempt by the company to make their sustainability messages explicit and provide greater legitimacy of activities and performance with the ultimate aim of enhancing organisational value. Research limitations/implications: This study contributes towards an in-depth understanding of attempts at seeking legitimacy and creating organisational value through the systematic usage of photographic disclosures in sustainability reporting. Practical implications: This study has the potential to inform stakeholders on linkages between sustainability photographs, value creation and legitimacy. It can help inform and assist report preparers, designers and users on the potential of photographs as a substantive medium to manage legitimacy in sustainability reporting. Originality/value: This paper adds to the scant literature on the growing use of photographs as a value adding apparatus in sustainability reporting. This paper also extends the applicability of legitimacy theory to visual disclosure and suggests that legitimacy can be systematically sought to create value.